Digital resilient narratives. Pedagogic gender frailties crossing time and space in emergency - Patrizia Garista; Cristina Coccimiglio (Firenze University Press, 2022)
In times of crisis, vulnerable groups face more challenges and experience a greater sense of exclusion, due to being separated from positive relationships, caregivers, supporters. A challenge that many women face is having multiple identities as mothers, workers, wives, caregivers. However, fragility can become the wheel of positive change if well supported by technologies and appropriate educational strategies. We know how narratives can serve to hold all these identities together, creating a digital space, where everyone can recognize similar stories or share their own. This article proposes a theoretical reflection on gender frailties during the time of the pandemic, and reflects on spaces and time which generate digital resilient narratives.   Narrazioni digitali resilienti. Le fragilità educative al femminile attraversano spazi e tempi dell'emergenza. In tempo di crisi, i gruppi vulnerabili devono affrontare più sfide e vivere di più la dimensione dell'esclusione, lontani da relazioni positive, caregivers, sostenitori. Tra loro, le donne si trovano a dover agire con le loro molteplici identità di madri, lavoratrici, mogli, caregivers. Tuttavia, la fragilità può essere riscattata se supportata da tecnologie e strategie educative e formative adeguate. Soprattutto sappiamo come le narrazioni condivise anche digitalmente creino uno spazio dove ognuno può riconoscere storie simili o condividerne una propria. Questo articolo propone una riflessione teoretica sulle fragilità attraverso uno sguardo di genere durante il periodo della pandemia, riflettendo su spazi e tempi che generano narrazioni resilienti digitali.